In vivo viability of stored red blood cells derived from riboflavin plus ultraviolet light-treated whole blood - Cancelas, Jose A.; Rugg, Neeta; Fletcher, Dana; Pratt, P. Gayle; Worsham, D. Nicole; Dunn, Susan K.; Marschner, Susanne; Reddy, Heather L.; Goodrich, Raymond P. (Transfusion (Philadelphia, Pa.), 2011)
BACKGROUND: A novel system using ultraviolet (UV) light and riboflavin (Mirasol System, CaridianBCT Biotechnologies) to fragment nucleic acids has been developed to treat whole blood (WB), aiming at the reduction of potential pathogen load and white blood cell inactivation. We evaluated stored red blood cell (RBC) metabolic status and viability, in vitro and in vivo, of riboflavin/UV light–treated WB (IMPROVE study). STUDY DESIGN AND METHODS: The study compared recovery and survival of RBCs obtained from nonleukoreduced WB treated using three different UV light energies (22, 33, or 44 J/mLRBC). After treatment, WB from 12 subjects was separated into components and tested at the beginning and end of component storage. After 42 days of storage, an aliquot of RBCs was radiolabeled and autologously reinfused into subjects for analysis of 24‐hour recovery and survival of RBCs. RESULTS: Eleven subjects completed the in vivo study. No device‐related adverse events were observed. By Day 42 of storage, a significant change in the concentrations of sodium and potassium was observed. Five subjects had a 24‐hour RBC recovery of 75% or more with no significant differences among the energy groups. RBC t1/2 was 24 ± 9 days for the combined three groups. Significant correlations between 24‐hour RBC recovery and survival, hemolysis, adenosine triphosphate (ATP), and CO2 levels were observed. CONCLUSIONS: This study shows that key RBC quality variables, hemolysis, and ATP concentration may be predictive of their 24‐hour recovery and t1/2 survival. These variables will now be used to assess modifications to the system including storage duration, storage temperature, and appropriate energy dose for treatment.